Multidrug-resistant non-typhoidal Salmonella enterica from chickens, farmworkers, and environments: One health implications from Northwestern Ethiopia - Azeb Bayu Mengistu; Mequanint Addisu Belete; Habtamu Tassew; Haregua Yesigat Kassa; Beyenech Gebeyehu Alemu; Hailehizeb Cheru Tegegne; Demelash Areda (PLoS ONE, 2025)
Non-typhoidal Salmonella are important foodborne zoonotic pathogens closely linked to poultry and poultry products. Despite their public health importance, limited data are available on the epidemiology and antimicrobial resistance patterns of nontyphoidal Salmonella in poultry production systems in Ethiopia. This cross-sectional study aimed to estimate the prevalence, identify risk factors, and assess the antimicrobial resistance profiles of Salmonella enterica from poultry farms in Bahir Dar city, northwestern Ethiopia. Standard bacteriological methods, PCR-based detection, and serotyping were used to investigate the presence of Salmonella in chicken (n = 126), environmental (n = 198), and human (n = 45) samples collected from 22 poultry farms. Antimicrobial susceptibility profiles were determined using the Kirby–Bauer disk diffusion method. Data from questionnaires and Fisher’s exact tests were used to identify risk factors associated with the occurrence of Salmonella. Nontyphoidal Salmonella species were detected on 18.1% (4/22) of the farms. Salmonella enterica was recovered from 3.1% (6/198) of environmental boot samples, 3.2% (4/126) of cloacal swabs, and 4.4% (2/45) of human stool samples. Two Salmonella serotypes were identified from among 12 Salmonella isolates: S. Enteritidis (41.6%, 5/12) and S. Typhimurium (16.6%, 2/12). All Salmonella isolates demonstrated complete resistance to ampicillin (100%) and tetracycline (100%) and exhibited multiple drug resistance patterns, with a high multiple antibiotic resistance index ranging from 0.45 to 0.55. The prevalence of Salmonella was significantly associated with the absence of foot baths (p = 0.0096) and the presence of other animal species on the farm (p = 0.026). The demonstrable emergence of multidrug-resistant Salmonella Enteritidis and Salmonella Typhimurium serotypes, alongside key factors driving the prevalence of nontyphoidal salmonellosis on poultry farms in northwestern Ethiopia, underscores the need for improved intervention strategies and ongoing large-scale One Health genomic surveillance to accurately monitor temporal dynamics of Salmonella infections and mitigate the rise of multidrug resistance.